2015
DOI: 10.3390/ijms161226119
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotency and Gene Editing in Disease Modelling: Perspectives and Challenges

Abstract: Embryonic stem cells (ESCs) are chiefly characterized by their ability to self-renew and to differentiate into any cell type derived from the three main germ layers. It was demonstrated that somatic cells could be reprogrammed to form induced pluripotent stem cells (iPSCs) via various strategies. Gene editing is a technique that can be used to make targeted changes in the genome, and the efficiency of this process has been significantly enhanced by recent advancements. The use of engineered endonucleases, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 148 publications
(188 reference statements)
0
17
0
Order By: Relevance
“…Previous studies have reported the application of the genome-editing technique in the human pluripotent stem cells to model diseases that were caused by single-gene mutations for drug discovery [30,31]. In the present study, we generated GLA-null HEK-293T cell lines by CRISPR/Cas9 genome-editing system.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have reported the application of the genome-editing technique in the human pluripotent stem cells to model diseases that were caused by single-gene mutations for drug discovery [30,31]. In the present study, we generated GLA-null HEK-293T cell lines by CRISPR/Cas9 genome-editing system.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the tools of precise genome editing with engineered nucleases, such as the zinc finger nucleases (zfns), the transcription activator-like effecter nucleases (talens) and, more recently, the Clustered Regularly Interspaced Short Palindromic Repeats (crispr) associated Cas9 technology (Gaj, Gersbach and Barbas, 2013;Kim, 2016;Komor, Badran and Liu, 2017) have opened up tremendous opportunities for the development of cell lines, especially those of human origin (Tobita, Guzman-Lepe and de L'Hortet, 2015). crispr/Cas9 technology was reported for genome editing in hiPSCs (Flaherty and Brennand, 2015;Li et al, 2014;Seah et al, 2015;Suzuki et al, 2014). Another study reported on the simultaneous reprogramming and gene correction of patient fibroblasts (Howden et al, 2015).…”
Section: Toxicology In the 21st Centurymentioning
confidence: 99%
“…Image courtesy of the Wyss Institute, Harvard University .8 Modern cell reprogramming and gene editing tools, allowing modifications of patient-specific iPSCs for use in disease research, toxicology, and screening, in addition to the possibility of cell therapy. Image taken fromSeah et al (2015)…”
mentioning
confidence: 99%
“…By contrast, in HDR, a sequence of DNA that is partially homologous (typically the undamaged homologous chromosome) serves as a template for repair (Figure 1). Alternatively, if a DSB occurs in the presence of an exogenously introduced homologous repair template, the addition of specific DNA sequences can occur [51] (Figure 1). …”
Section: Endogenous Repair Of Double-stranded Dna Breaks (Dsb)mentioning
confidence: 99%